Currículo, escola e letramento: o que isso tem a ver com a formação do cidadão? - Barbosa, Ezequiel Ferreira; Müller, Maria Candia (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This paper aims to present some considerations about curriculum and its importance to the adoption of an educational practice that breaks with old paradigms, considering that the concept adopted and practiced in schools has become a hindrance to the realization of a work that takes students to be agents of their own learning and, consequently, conscious citizen entered in a world in constant transformation. It also approach the issue of literacy as a daily practice in schools, reflecting the training for citizenship. It also seeks to show that the area of language skills is a condition without which learning is compromised and that these skills that go far beyond the simple act encode and decode words and a task that is the responsibility of all teachers, not just the mother language.